Editorial - Atencio Vargas, Aracadio (2019)
Research is a set of systematic, critical and empirical processes that apply to the study of a phenomenon or problem (Hernández Sampieri, Fernández Collado, and Baptista Lucio, 2010). Precisely, this vital process in academic work corresponds to the university through its different faculties, teachers, students and graduates. In the route drawn by University Law No. 30220 regarding the role of the Peruvian University, the Faculty of Engineering of the Private University of Tacna, relaunches its research processes as a fundamental pillar in the development of its goals; the investigation. An additional fact is the dissemination of its activities in this field, for this purpose the scientific journal "Engineering Research" is presented. In recent years, the Faculty of Engineering financed various investigations through project competitions, the results of these investigations will be reflected in this magazine and, without fear of being wrong, are contributions to society in their respective field of action. The Faculty of Engineering considers research as the nexus to solve the problems of society, an inevitable task of the modern university in its knowledge-creating role that progress demands, in that direction, engineering also defines as typical of its activity, the transformation of ideas into realities, therefore the magazine "Engineering Research" is created with the commitment to become an interdisciplinary space where our university academic community and invited researchers independently or on behalf of other institutions, can disseminate progress and scientific and technological results of their research. The magazine Ingeniería Investiga, will disseminate research on the programs of System Engineering, Civil Engineering, Electronic Engineering, Environmental Engineering, Industrial Engineering and Agroindustrial Engineering, and related branches in the field, will have a semi-annual publication character; This forces us to continue working and motivating scientific production that provides solutions to national and international society.